INNOVATIVE TECHNOLOGIES IN ENSURING IDEOLOGICAL SECURITY IN FOREIGN COUNTRIES (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
In the context of globalization processes and the digital revolution, the issue of ideological security has become one of the fundamental factors determining the internal stability, sovereignty, and development strategy of every state. The crossing of information flows beyond national borders, the rapid and unrestricted nature of digital communication, and the increasingly complex character of hybrid ideological threats necessitate a radical rethinking of approaches to ideological security.